Effects of chickpea protein fractions on α-amylase activity in digestion. (December 2022) - Tan, Xiaoyan; Zhang, Shaobo; Malde, Alpeshkumar K.; Tan, Xinle; Gilbert, Robert G.
Abstract: This study concerns the effects of endogenous proteins on starch digestion kinetics. It investigates the effects in chickpeas of hydrolysates released from the endogenous proteins albumin, globulin and glutelin on the in vitro activity of porcine pancreatic α-amylase (PPA) and on starch digestion. Using a docking simulation, potential proteinaceous α-amylase inhibitors (α-AIs) belonging to the small peptides of albumin, globulin and glutelin are identified and their binding mechanisms with PPA are explored. It was found that cooking and pepsin hydrolysis led to severe degradation of protein fractions, accompanied by the enrichment of small (<10 kDa) peptides, among which peptides <3 kDa exhibited strong inhibitory activity (up to 50%). Most of the active α-AIs were therefore considered to be found in the fractions <3 kDa, and were further characterized by mass spectrometry combined with in silico analysis. Docking results showed that glutelin could produce the most α-AIs (45 peptides), followed by globulin (41) and albumin (12). Among these, 71 peptides were predicted to exhibit a competitive or uncompetitive type of inhibition on PPA, whereas 6 peptides performed a noncompetitive inhibition. The competitive and uncompetitive α-AIs inhibited enzyme activity mainly by binding to a flexible loop and three major catalytic residues in PPA, and the latter by interacting with the non-catalytic regions of PPA. Different inhibition types therefore can together to hinder the formation of enzyme-starch complexes, so that PPA activity is inhibited and starch digestibility could be reduced. Graphical abstract: Image 1 Highlights: Chickpea proteins reduce starch digestion rate, which is nutritionally advantageous. Cooking and pepsin hydrolysis produced albumin-, globulin- and glutelin-peptides. Peptides<3 kDa had the highest α-amylase inhibitory activity. 77 peptides were predicted to be α-amylase inhibitors. Inhibitors exhibited competitive, uncompetitive and noncompetitive inhibition.